Evaluation of Healthy Cantine Program in Elementary School - Hendro Widodo; Feli Feli (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2021)
This research aims to evaluate the context, input, process, and product program of the Muhammadiyah Suronatan elementary school health canteen program. This study is an evaluative study with the CIPP model. Data collection techniques used interview, observation, and documentation techniques. The respondents of this study are the principal, the teacher in charge of the canteen, the canteen manager, and students. Some of the steps taken in data analysis include data collection, reduction, presentation, and conclusion. The results showed four main components. First, the school canteen aims to provide safe, healthy, and nutritious food from the context aspect. Second, it is appropriate to improve students’ health through human resource support and adequate funds based on the input aspect. Third, the school has held clean and healthy living socialization for school residents based on the process aspect. Lastly, in terms of product, all the targets from the planned program have been achieved.